Entropy squeezing of multi-photon field interacting with a single Cooper-pair box - Kadry, H. (Springer Science and Business Media B.V., 2014)
We investigate the entropy squeezing and entanglement of the Cooper-pair box interacting with multi-photon cavity field. The field is prepared initially in the coherent state, while the Cooper-pair box is assumed to start from a mixed state. We find that the number of photons and the detuning parameters play an important role in the entropy squeezing and entanglement. We observe that the entropy squeezing can be used as a good indicator of the entanglement. This study opens promising perspectives for creating remote quantum information processing networks. Â© 2014 Elsevier GmbH. All rights reserved.